2018
DOI: 10.5194/wes-3-221-2018
|View full text |Cite
|
Sign up to set email alerts
|

Ducted wind turbine optimization and sensitivity to rotor position

Abstract: Abstract. The design of a ducted wind turbine modeled using an actuator disc was studied using Reynolds-averaged Navier–Stokes (RANS) computational fluid dynamics (CFD) simulations. The design variables included the rotor thrust coefficient, the angle of attack of the duct cross section, the radial gap between the rotor and the duct, and the axial location of the rotor in the duct. Two different power coefficients, the rotor power coefficient (based on the rotor swept area) and the total power coefficient (bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…The k −ω shear stress transport (SST) turbulence model was utilized, which, among the twoequation turbulence models, gives better prediction of flow separation. Further details of the methods employed can be found in Bagheri-Sadeghi et al (2018), and an example of the solution is shown in Fig. 5a.…”
Section: Numerical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The k −ω shear stress transport (SST) turbulence model was utilized, which, among the twoequation turbulence models, gives better prediction of flow separation. Further details of the methods employed can be found in Bagheri-Sadeghi et al (2018), and an example of the solution is shown in Fig. 5a.…”
Section: Numerical Approachmentioning
confidence: 99%
“…The last curve on the plot, denoted by the heavy dashed line, is the numerical prediction by the actuator disk model in FLUENT, namely the solution used to generate the input velocity field profile for the mRotor design. The power predicted repre- Bagheri-Sadeghi et al (2018). The C p values, based on the rotor area, were also calculated for the data and are presented in Fig.…”
Section: Power Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Achieving values of C P,total greater than the Betz's limit of 0.593 for a DWT is significant as it means a DWT can capture more power per unit area of the device than an open rotor turbine. Optimization studies of DWTs have shown that DWTs can achieve values of C P,total beyond Betz's limit (Aranake and Duraisamy, 2017;Bagheri-Sadeghi et al, 2018). C P,total not only is a useful metric to compare DWTs with open rotor wind turbines but could be an important design objective in certain problems like fully-integrated DWTs for sustainable 1 https://doi.org/10.5194/wes-2021-18 Preprint.…”
Section: Introductionmentioning
confidence: 99%
“…Since the experimental demonstration of the power augmentation provided by shrouding wind turbines (Sanuki, 1950), numerous studies on the design and optimization of the DWTs have been carried out (Lilley and Rainbird, 1956;Igra, 1981;Loeffler, 1981;Gilbert and Foreman, 1983;Georgalas et al, 1991;Politis and Koras, 1995;Hansen et al, 2000;Phillips et al, 2002;Ohya and Karasudani, 2010;Aranake and Duraisamy, 2017;Venters et al, 2018;Bagheri-Sadeghi et al, 2018). Only a few (Aranake and Duraisamy, 2017;Bagheri-Sadeghi et al, 2018;Venters et al, 2018) have used C P,total as a design metric while most other studies have focused on maximizing C P . The design variables of a DWT include the rotor blade design, its axial location, z rotor , and tip clearance or rotor gap, ∆n, and the angle of attack, α, length, l, and shape of the duct crosssection.…”
Section: Introductionmentioning
confidence: 99%